Water use and productivity of two small reservoir irrigation schemes in Ghana's upper east region - Faulkner, J.W.; Steenhuis, Tammo S.; Giesen, Nick van de; Andreini, Marc; Liebe, Jens R. (2008)
To examine the impact of small reservoir irrigation development in Africa, the performance and productivity of two small reservoirs and irrigation schemes in the Upper East Region of Ghana were investigated in this study. Hydrologic data measured included daily irrigation volumes and daily evaporation. Farmer cost inputs, excluding labor, and harvest data were also recorded. There was a strong contrast in water availability between the two systems, the Tanga system having a higher amount of available water than did the Weega system. The concept of relative water supply was used to confirm this disparity; Tanga was an inefficient system with a relative water supply of 5.7, compared to a value of 2.4 for the efficient Weega system. It was also concluded that the dissimilar water availabilities resulted in the evolution of very different irrigation methods and coincided with different management structures. Where there was more water available per unit land (Tanga), management was relaxed and the irrigation inefficient. Where there was less water available per unit land (Weega), management was well structured and irrigation efficient. The productivity of water (US$ m_3) of the Tanga system was half that of the Weega system, when analyzed at a high market price for crops grown. In terms of productivity of cultivated land (US$ ha_1), however, the Tanga system was 49% more productive than the Weega system. The difference in the productivity of land is primarily a result of increased farmer cash inputs in the Tanga system as compared to the Weega system. The difference in the productivity of water can be attributed to the varying irrigation methods and management structures, and ultimately to the contrasting water availability.